Sensitivitas dan Spesifisitas pada Isolat Bakteri Carbapenem-Resistant Klebsiella pneumoniae (CRKP) dengan Metode Real-Time PCR - Aisyah Khairani; Linosefa Linosefa; Endrinaldi Endrinaldi (Fakultas Kedokteran, Universitas Andalas, 2026)
Abstract Background. Infectious diseases are among the leading causes of death in the world with high morbidity and mortality rates. Increasing resistance in infectious bacteria such as Klebsiella pneumoniae to carbapenem antibiotics is certainly a major health problem. Objective. The research aims to conduct sensitivity and specificity tests on carbapenem-resistant Klebsiella pneumoniae (CRKP) bacterial isolates molecularly using the Real-Time PCR method. Methods. The type of research included descriptive research using a diagnostic test approach. The samples used in this study were Klebsiella pneumoniae bacterial isolates that were resistant to carbapenem antibiotics, namely meropenem, which had been tested for sensitivity through bacterial culture as the gold standard. The technique used in sampling was consecutive sampling which was collected according to the inclusion criteria until the minimum number of samples was met, which was 81 bacterial isolates. Results. The distribution of CRKP encoding genes found in bacterial isolates is blaNDM with a percentage of 38.27% and neither blaKPC nor blaOXA was found. The results of diagnostic tests on CRKP bacterial isolates with Real-Time PCR method obtained a sensitivity value of 89.28%, specificity 88.67%, accuracy 88.88%, positive predictive value 80.64% and negative predictive value 94%. Conclusion. The conclusion of this study is that the results of diagnostic tests on CRKP bacterial isolates molecularly by Real-Time PCR method have sensitivity, specificity, accuracy /precision, positive predictive value and negative predictive value which are quite high and more efficient (does not require a long examination time). Keyword: Carbapenem-Resistant Klebsiella pneumoniae, Klebsiella pneumoniae, Resistant, Antibiotics, Real-Time PCR, Sensitivity, Specificity.